(untitled) (Research, Society and Development, 2022)
Introduction: Eating habits can contribute to or harm the quality of life of individuals. This can be observed in the development of Type 2 Diabetes Mellitus, which currently stands out among the Chronic Noncommunicable Diseases (NCDs). Thus, the importance of analyzing the influence that food has on the development and benefits of this pathology is highlighted. Objective: To analyze the perception of diabetics in relation to dietary intervention as a cause and treatment of DM2. Methodology: This is a literature review with an integrative method. Results: Based on the study of the literature, it was possible to deepen the knowledge of risk factors for the development of type 2 diabetes mellitus, as well as its health implications. Therefore, the importance of acquiring knowledge about food intervention for both prevention and treatment was presented, focusing on the vision of DM2 patients and the level of adherence to treatment. Conclusion: It was found that even with the knowledge acquired here in relation to the perception of food intervention as a negative / positive point in question DM2, there is still a need for specific guidelines.